Introduction and Review of Techniques, Applications, and Limitations of Solid Phase Microextraction Method - Sara Karimi-Zeverdegani; Zohreh Mohebian; Samane Khorshidikia (تحقیقات نظام سلامت, 2023)
Solid phase microextraction (SPME) is a sub-sample extraction method that has been developed to solve some of the challenges associated with sample preparation as well as to integrate different stages of analysis into one system. SPME is a solvent-free, cost-effective, efficient, and high-performance sample preparation technique. This technique combines all the extraction steps into one step. In the recent years, combining SPME with analysis tools has been very efficient for sampling and analyzing multiple compounds and a lot of research has been done on the benefits, applications, and advancements of this technique. This study also introduces SPME along with its various aspects and fields of application.